MEMBANGUN Ã¢â‚¬Å“SISTEM DINAMIS UNTUK MENGHITUNG DEBIT PUNCAKÃ¢â‚¬Â (SDDP) DENGAN MENGGUNAKAN STELLA VERSI 9.0.2 (Uji Aplikasi Untuk Wilayah Banjir di Kecamatan Makasar Jakarta Timur) - Indriatmoko, Robertus Haryoto (Center for Environmental Technology, 2009)
Peak Discharge Dinamyc System (SDDP) is a program which apply to calculate peak of discharge a catchment area with area and rain fall intensity as parameters, with limited to maximal 50 km2 area and 100 mm/hour rain fall intensity. This program is develop by using System Dinamyc Stella version 9.0.2. Steps taken are, first by calculate runoff cooeficient use Bridge-Branch method and then calculate peak discharge with rational method. This program is tested on sub-catcment Makassar, East Jakarta and compare the result of the program with manual calculation, and concluded that no deviation between those 2 methods, and even more the SDDP program provide prediction of peak discharge with variable C value and data of calculation peak discharge with SDDP program presented in graphic and tabulation as well.Ã‚Â Key words : Model, Sistem Dinamis, Stella, Banjir, Debit Puncak, Koefisien Aliran, Prediksi, Jakarta Timur